1996
DOI: 10.1021/ja942053k
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Deuterium Isotope Effects for Enolization Reactions

Abstract: Secondary R-and β-deuterium isotope effects for enolization reactions and equilibria have been determined by ab initio calculations, 1 H NMR spectroscopy, and triton exchange kinetics. Kinetic and equilibrium R-deuterium isotope effects for hydroxide ion-catalyzed enolization of acetaldehyde calculated by ab initio methods are normal and depend on the orientation of the secondary hydrogen with respect to the carbonyl group. The computed transition state structure indicates a small degree of bond rehybridizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 65 publications
(52 reference statements)
4
46
0
Order By: Relevance
“…Limited attempts to account for the influence of the solvent on isotope effects at the microscopic level have been reported previously. 37,38 Inclusion of a single 37,38 or two 38 water molecules was found to improve the calculated H/D EIE on enolization of acetaldehyde 37 and the 16 O/ 18 O KIE on decarboxylation of 4-pyridylacetic acid zwitterion. 38 A comparison of microscopic and macroscopic approaches in the latter study 38 showed that the SM5.42 continuum solvent model 39 gave significantly better energetic results than the two-water cluster representation, while the obtained KIEs were of similar accuracy with the discrete and continuum representations.…”
Section: Discussionmentioning
confidence: 94%
“…Limited attempts to account for the influence of the solvent on isotope effects at the microscopic level have been reported previously. 37,38 Inclusion of a single 37,38 or two 38 water molecules was found to improve the calculated H/D EIE on enolization of acetaldehyde 37 and the 16 O/ 18 O KIE on decarboxylation of 4-pyridylacetic acid zwitterion. 38 A comparison of microscopic and macroscopic approaches in the latter study 38 showed that the SM5.42 continuum solvent model 39 gave significantly better energetic results than the two-water cluster representation, while the obtained KIEs were of similar accuracy with the discrete and continuum representations.…”
Section: Discussionmentioning
confidence: 94%
“…II, we describe a rigorous quantum-mechanical methodology to compute the EIE. Section III presents the [1,5] sigmatropic hydrogen shift reactions on which we test the methodology, explains how ab initio methods can be combined with the PI to compute the EIE, and discusses in detail symmetry effects in these reactions. Section IV explains the implementation of the method in Amber 10 and describes details of calculations and error analysis of our PIMD simulations.…”
Section: Introductionmentioning
confidence: 99%
“…We describe the implementation of the methodology in the molecular dynamics package Amber 10. The method is tested on three [1,5] sigmatropic hydrogen shift reactions. Because of the computational expense, we use ab initio potentials to evaluate the equilibrium isotope effects within the harmonic approximation, and then the path integral method together with semiempirical potentials to evaluate the anharmonicity corrections.…”
mentioning
confidence: 99%
“…The frequency calculations on the stationery points for the enolate-forming reaction were also use to calculate deuterium kinetic isotope effects, the results of which are presented elsewhere. 24 Monte Carlo simulations were performed on an isothermal-isobaric ensemble consisting of the reacting system plus 263 water molecules in a cubic box with dimensions ca 20 x 20 x 20 A3. Periodic boundary conditions were employed.…”
Section: Methodsmentioning
confidence: 99%